2017
DOI: 10.5152/dir.2017.17004
|View full text |Cite
|
Sign up to set email alerts
|

Lesion characteristics, histopathologic results, and follow-up of breast lesions after MRI-guided biopsy

Abstract: M agnetic resonance imaging (MRI) is a widely used diagnostic tool for breast imaging in daily practice, with its high sensitivity to detect primary, recurrent, and residual breast cancer. Breast MRI serves as a reliable problem-solving tool in case of inconclusive mammography and ultrasonography (US) findings. It can be used to monitor the results of neoadjuvant chemotherapy and it may also contribute to preoperative evaluation of known lesions. With increasing use of MRI, number of breast lesions visible onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The malignancy rate in this study of women with MRI-visible breast lesions who underwent MRI-guided wire localization with subsequent surgical biopsy and MRI-guided biopsy of breast minimal lesions was 40.91% (in 13 patients who underwent MRI-guided biopsy, the malignancy rate was 23.08%, and in 74 patients with 75 eligible lesions who underwent MRI-guided wire localization with surgical biopsy, the malignancy rate was 44.0%), which is higher than the reported range of 20-35% (22)(23)(24)(25). The main difference in this study was that the majority of patients (n = 74) underwent MRI-guided wire localization with subsequent surgical biopsy (the number of suspicious lesions was 75), and only 13 patients underwent MRI-guided biopsy.…”
Section: Discussionmentioning
confidence: 74%
“…The malignancy rate in this study of women with MRI-visible breast lesions who underwent MRI-guided wire localization with subsequent surgical biopsy and MRI-guided biopsy of breast minimal lesions was 40.91% (in 13 patients who underwent MRI-guided biopsy, the malignancy rate was 23.08%, and in 74 patients with 75 eligible lesions who underwent MRI-guided wire localization with surgical biopsy, the malignancy rate was 44.0%), which is higher than the reported range of 20-35% (22)(23)(24)(25). The main difference in this study was that the majority of patients (n = 74) underwent MRI-guided wire localization with subsequent surgical biopsy (the number of suspicious lesions was 75), and only 13 patients underwent MRI-guided biopsy.…”
Section: Discussionmentioning
confidence: 74%
“…MRI-guided wire localization is an important intervention method, which is based on careful radiological analysis and accurate evaluation of BI-RADS Class 4 and above lesions. The overall malignant rate for MRI-guided wire localization ranges from 20% to 35% in European and American countries (21)(22)(23)(24). The malignant rate of MRI-guided biopsy was 43% in 185 women with high risk of breast cancer according to Miah et al in 2023 (25).…”
Section: Discussionmentioning
confidence: 99%
“…There was a statistical correlation between the enhancement pattern of lesions and the malignancy rate in the reports of Macura et al (32), Dratwa et al (33), and Moreno et al (34) involving 541 MRI biopsy cases; they found that it was difficult to assess whether the lesion was benign or malignant based on simple enhancing morphology (NME, EM, or EF); however, the early rapid inflow (p = 0.038) and delayed outflow hemodynamics (p = 0.032) of DCE-MRI were significantly correlated with malignancy. Myers et al's (21) research findings suggested that the malignant rate was related to the "outflow" of TIC. In this study, the statistical correlation of benign or malignant lesions involved hemodynamics (TIC curve), rather than the morphological enhancement (EF, EM, and NME).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, widespread adoption of breast MRI in clinical practice has led to increased biopsy rates but diminished diagnostic yield (8). Recent studies have shown that the large majority (65-74%) of suspicious breast MRI lesions investigated with MRI-guided CNB are benign (65-74%) (16)(17)(18) with the most common pathologic diagnosis being FCC.…”
Section: Discussionmentioning
confidence: 99%